Burkina Faso : Second Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Burkina Faso's Second Review of the Extended Credit Facility (ECF) Arrangement and Request for a Waiver of Nonobservance of a Performance Criterion. Performance under the ECF-supported program has been broadly satisfactory. Economic activity remains resilient in the face of increased security and social tension pressures. Growth in 2018 remained resilient as a bumper harvest more than compensated for a decline in nonagricultural gross domestic product growth. Burkina Faso continues to pursue its development goals, and further support from the international community to address security and development needs is important. Additional effort is required to create fiscal space to support further progress in priority areas of development. The authorities are taking steps to strengthen the implementation of the automatic fuel price adjustment mechanism while developing social safety nets for the most vulnerable. In this respect, greater transparency, improved communication and the avoidance of discretionary implementation of the mechanism are crucial.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet